The path to the construction of a domestic and international dual cycle of China’s shipping industry - Cao, Xingguo; Zhang, Xu; Chang, Yen-Chiang (Frontiers in Marine Science, 2023)
Being the adjustment of the development strategy of the People’s Republic of China (hereinafter referred to as the “PRC”), the new domestic and international dual-cycle development pattern forms the policy framework and target of the PRC’s future shipping industry. By exam the policy innovations taken in the Pilot Free Trade Zones/Free Trade Port and high-level Free Trade Agreements signed by PRC, this paper provides a conceptual research on the path to the construction of a domestic and international dual cycle of the PRC’s shipping industry. It is argued that the internal shipping policy innovations and international agreements has laid the foundation of the path, but resistance such as weak modern shipping service industry, unattractive international shipping system, and myriad of uncertain factors and challenges need to be addressed. It is deemed necessary to optimize the deployment of shipping industry in the logistic system and strengthen the innovation of new development model with combination of digital technologies.